Informal sector employment, food security and vulnerability of households in Addis Ababa, Ethiopia - Seleshi, S.; Alemu, B.A.; Hanjra, Munir A. (2013)
People across Africa are urbanizing and cities act as magnets that attract poor migrants from rural areas, looking for employment and better life. During the last few decades, the informal sector has been growing fast in Addis Ababa, Ethiopia due to the influx of many young workers into the sector who come from rural areas of the country with the expectation of a better life in the city. The informal sector employment includes casual, temporary jobs such as lottery selling, street vending, petty trade and other similar activities - coping strategies and earning strategies to escape food poverty. The informal sector is believed to play an important role in food security as it provides jobs, reduces unemployment, bolsters economic activity, and helps alleviate poverty. However, there is limited local knowledge about the role of this sector in enhancing food security and reducing vulnerability of the emigrants. There is also limited research about the problems and prospects of the informal sector, and via-a-vis its potential contribution towards food security. Therefore, this research was conducted with the major objective of examining the food security level and vulnerability status of emigrants worker and their households to identify the major challenges and prospects for future policy interventions. Primary data were collected from 240 respondents (60 from each of the four sub-cities) who were selected randomly. Secondary data were also collected from government offices. Data were analyzed using both descriptive and econometric approaches. Probit model was used to determine food security status of respondents; whereas ordered probit model was used to identify the factors affecting their vulnerability level. Results suggest that the daily life of the majority of migrants in Addis Ababa (most of them are young school dropouts) is highly connected with street-based informal economic activities such as marketing, vending and lottery selling, etc. Results show that the annual mean income a household would earn is Eth. Birr 7,786.2 ($442). Results of the vulnerability analysis show that informal activities in the study area serve migrants only as temporary safety nets, not as sustainable earnings/livelihood strategies. Results further show that lack of access to bank credit (due to collateral requirements), fluctuating market prices and lack of working premises impacts their work. Data shows that the workers are forced to consume less food or poor quality food. Therefore, future urban policy may need to give due consideration to informal sector employment in order to realize synergies between the formal and informal sectors for addressing food security and poverty issues.